2005
DOI: 10.1007/bf02506876
|View full text |Cite
|
Sign up to set email alerts
|

A martingale approach to scan statistics

Abstract: Abstract. Scan statistics are commonly used in biology, medicine, engineering and other fields where interest is in the probability of observing clusters of events in a window at an unknown location. Due to the dependent nature of the number of events in a large number of overlapping window locations, even approximate solutions for the simplest scan statistics may require elaborate calculations. We propose a new martingale method which allows one to approximate the distribution for a wide variety of scan stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Because of the practical importance the occurrence of patterns has been studied extensively by many different techniques. Here is a list of some recent works in the area: Antzoulakos (2001), Chang (2005), Fu (2001), Fu and Chang (2002), Fu and Lou (2006), Hirano and Aki (2003), Pozdnyakov et al (2005), Rukhin (2002) and Stefanov (2000Stefanov ( , 2003. Useful reviews of different approaches can be found in two recent books: Balakrishnan and Koutras (2002) and Fu and Lou (2003).…”
Section: Introductionmentioning
confidence: 97%
“…Because of the practical importance the occurrence of patterns has been studied extensively by many different techniques. Here is a list of some recent works in the area: Antzoulakos (2001), Chang (2005), Fu (2001), Fu and Chang (2002), Fu and Lou (2006), Hirano and Aki (2003), Pozdnyakov et al (2005), Rukhin (2002) and Stefanov (2000Stefanov ( , 2003. Useful reviews of different approaches can be found in two recent books: Balakrishnan and Koutras (2002) and Fu and Lou (2003).…”
Section: Introductionmentioning
confidence: 97%
“…The initial arguments of Pozdnyakov et al (2005) in favor of the shifted exponential approximation were predominantly empirical, but subsequently a more theoretical motivation has emerged from work of Fu and Lou (2006, p. 307) which shows that for large n one has…”
Section: Second Moments and Distribution Approximationsmentioning
confidence: 99%
“…A martingale approach (see Gerber and Li [14], Li [19], Williams [32]) is an alternative to the Markov chain embedding method to solve problems around Penney [21] Game. These two approaches are compared in Pozdnyakov et al [24]. Whatever method one uses, the distribution of the first occurence of a word strongly depends on its overlapping structure.…”
Section: Remark 12mentioning
confidence: 99%